Effects of local nitrogen supply and nitrogen fertilizer variety coupling on rice nitrogen transport and soil nitrogen balance in paddy fields - Hu, Ren; Xiao, Dakang; Ding, Zijuan; Cao, Yuxian; Hou, Jun; Wang, Xuexia (Frontiers in Sustainable Food Systems, 2023)
Introduction This study aimed to provide the theoretical basis for formulating scientific and reasonable on-farm nitrogen (N) management measures and efficient strategic fertilization to understand the effects of localized N supply (LNS) and N fertilizer variety coupling on N transport and soil N balance in rice fields. Methods A 2-year field experiment (2020 and 2021) was conducted in Jingzhou, Hubei Province, which included the following six treatments: no N application (CK), farmers' fertilizer practice (FFP), and four LNS treatments, including two N application methods including mechanical side-deep fertilization (M) and root-zone fertilization (R), two N fertilizer types with urea (U), and controlled-release urea (CRU). Results Compared with FFP, LNS increased the N apparent translocation level from stems, sheathes, and leaves (TNT) and N uptake by 10.70–50.59% and 11.28–29.71%, respectively. In LNS, the levels of nitrite reductase (NR), glutamine synthetase (GS), and glutamate synthase (GOGAT) under R increased by 13.81, 9.56, and 15.59%, respectively, compared with those under M, resulting in a significant increase in TNT by 8.58% and N uptake by 1.87%. Regarding the N fertilizer type, CRU significantly increased chlorophyll content by 7.27%, superoxide dismutase (SOD) and catalase (CAT) by 14.78 and 29.95% (p < 0.05), and NR, GS, and GOGAT by 44.41, 16.12, and 28.41% (p < 0.05), respectively, compared with that in U, which contributed to N absorption and transport. Moreover, CRUR significantly decreased N apparent loss by 50.04% compared with CRUM (p < 0.05). Discussion Considering the risk of soil N leaching and environmental protection, R should be selected as the recommended fertilization method. The combination of CRU and R is the most effective fertilization approach.